2012
DOI: 10.1093/annonc/mdr435
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, risk factors, and outcomes of osteonecrosis of the jaw: integrated analysis from three blinded active-controlled phase III trials in cancer patients with bone metastases

Abstract: In this combined analysis of three prospective trials, ONJ was infrequent, management was mostly conservative, and healing occurred in over one-third of the patients. Educating physicians about oral health before and during bone-targeted therapy may help reduce ONJ incidence and improve outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
495
8
27

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 680 publications
(578 citation statements)
references
References 30 publications
20
495
8
27
Order By: Relevance
“…The approach to MRONJ should be multidisciplinary and include an appropriated dental evaluation before initiating the antiresorptive or antiangiogenic to reduce local risk factors (5,(14)(15)(16)(17)(18). Whenever MRONJ cannot be avoided, local treatment consists in eliminating the pain and control local infection.…”
Section: Mronj Was First Reported In 2003 But Its Pathophysiologymentioning
confidence: 99%
“…The approach to MRONJ should be multidisciplinary and include an appropriated dental evaluation before initiating the antiresorptive or antiangiogenic to reduce local risk factors (5,(14)(15)(16)(17)(18). Whenever MRONJ cannot be avoided, local treatment consists in eliminating the pain and control local infection.…”
Section: Mronj Was First Reported In 2003 But Its Pathophysiologymentioning
confidence: 99%
“…Such an increase in ONJ frequency highlights the need for longer patients' monitoring and the adoption of nonparametric actuarial estimation (Kaplan-Meier), as done in other studies [10] the integrated analysis of the results of three pivotal trials of blinded comparison between denosumab and zoledronic acid: they also reported the number of Bpotential ONJ^cases that were initially registered as spontaneously reported by investigators or on the base of 36 MedDRA (Medical Dictionary for Regulatory Activities) adverse oral event terms. BPotential ONJ^cases, defined by the presence of clinical sign and symptoms suggestive of ONJ, were three times higher than the finally Badjudicated ONJ^cases: 276/5723 (4.8 %) versus 89/5723 (1.5 %).…”
Section: To the Editormentioning
confidence: 99%
“…BPotential ONJ^cases, defined by the presence of clinical sign and symptoms suggestive of ONJ, were three times higher than the finally Badjudicated ONJ^cases: 276/5723 (4.8 %) versus 89/5723 (1.5 %). Of importance, such data were recorded after a relatively short observation time, being the median (Q1, Q3) time on study 12.1 (5.4, 19.4) months for patients in the ZA group and 12.6 (5.6, 19.4) months for patients in the denosumab group [10]. We believe that it would be of great value if the authors of the extension study [1] could report the number of Bpotential ONJ^cases (defined as above) observed in the breast and prostate cancer population of the extension study, and compare them with those of the blinded study, and those among patients who declined shift to denosumab, if available.…”
Section: To the Editormentioning
confidence: 99%
“…Longer duration of therapy, higher cumulative doses, treatment with more potent bisphosphonates (zoledronic acid and pamidronate), history of recent alveolar trauma and inflammatory dental disease are known risk factors for ONJ (Hoff et al, 2008;Hoff et al, 2011). Glucocorticoid treatment or antiangiogenic therapy may also contribute to ONJ development (Saad et al, 2012). Bisphosphonates accumulate in the bone and effect of denosumab on bone become reversible after several months.…”
Section: Safetymentioning
confidence: 99%